Optimizing the Role of Guidance and Counseling Teachers in the Transformation of 21st Century Education - Tiara Maiza Dianti; Firman; Riska Ahmad (Literasi Nusantara, 2022)
In the era of globalization, it has had quite a broad impact on various aspects of life, including demands on the implementation of education. So that education has a very important role in producing human resources who have complete competencies, known as 21st century competencies. The progress of science and technology is recognized as an implication of the results of educational development as well, has become a challenge in the implementation of education itself which produces competent human resources. Various efforts have been made in the field of education in transforming education that is capable of giving birth to human resources with character in the 21st century. Improving the quality and quality of guidance and counseling services in the 21st century is very important to be broken in order to produce quality counseling teacher professionalism as a service provider. So that it can realize good quality guidance and counseling services in the process of transforming education in the 21st century.